Photoinduced cholesteric helix inversion in some systems containing chiral α,β-unsaturated ketones - Krivoshey, A.I.; Shkolnikova, N.I.; Chepeleva, L.V.; Kutulya, L.A.; Pivnenko, N.S. (Functional Materials, 2004)
Cholesteric helix inversion induced with UV irradiation has been revealed in the liquid crystal (LC) system based on nematic 4-pentyl-4 '-cyanobiphenyl (5CB) which contains left-handed helix inducing chiral dopant of 3( R)-methyl-6-arylidenecyclohexanone series. A further irradiation results in increasing right-handed helical twisting in the system till photostationary state is reached. The twisting extent in this state exceeds three times that in the initial mixture and remains unchanged under further UV light action. The effect under consideration must be caused by reversible photochemical E,Z-isomerization of the chiral dopant molecules. This was proven by preparative photochemical synthesis of the corresponding Z-isomer and independent study of its properties as a chiral dopant in 5CB. It is shown that a principal difference exists between photoinduced changes in the LC systems containing chiral a,P-unsaturated ketones, 3(R)-methylcyclohexanone and (+)-isomenthone derivatives.